2015
DOI: 10.1016/j.bios.2014.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Development of electrochemical methods to enzymatically detect traumatic brain injury biomarkers

Abstract: As awareness of traumatic brain injury (TBI) increases, the need to detect mild forms and distinguish between the different severities of TBI becomes more apparent. The goal of this work is to develop a point-of-care sensor to detect whole blood biomarkers for rapid and sensitive diagnosis of TBI severity. Presented herein is the enzymatic detection of norepinephrine through the use of immobilization chemistry and impedance techniques. Sustained elevation of norepinephrine concentrations in the blood has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The 16 articles selected fall into two main categories: 8 clinical papers and 8 laboratory studies on animal models of TBI [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Briefly, the 8 clinical studies identified have described four main technologies for identification of predictive biomarkers: (a) Microvescicle/Exosome, (b) MicroRNA, (c) Mass Spectroscopy, and (d) Multiplexing and Immunoassays [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 16 articles selected fall into two main categories: 8 clinical papers and 8 laboratory studies on animal models of TBI [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Briefly, the 8 clinical studies identified have described four main technologies for identification of predictive biomarkers: (a) Microvescicle/Exosome, (b) MicroRNA, (c) Mass Spectroscopy, and (d) Multiplexing and Immunoassays [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the 8 clinical studies identified have described four main technologies for identification of predictive biomarkers: (a) Microvescicle/Exosome, (b) MicroRNA, (c) Mass Spectroscopy, and (d) Multiplexing and Immunoassays [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. On the other hand, the methodology of the 8 laboratory studies was based on (a) MicroRNA, (b) Mass Spectroscopy, and (c) Multiplexing and Immunoassays; those latter investigated several different animal models of TBI ranging from mild to severe TBI including blunt traumas and diffuse axonal injuries; a wide range of animals were investigated in those studies, they included small size animals such as mice and rats but also rabbits and larger size animals such as pigs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to detect efficacy following any intervention probably requires assessment of relevant biomarkers that would clearly assist diagnosis and outcome assessment. Although potential biomarkers have been identified in experimental and clinical TBI studies, 14 , 15 they are still lacking appropriate validation and implementation. 16 Ideally, clinical studies would contain a variety of measures in order to better characterize TBI and facilitate individualized treatment.…”
Section: Progesterone and Tbi – Comparing Experimental And Clinical Dmentioning
confidence: 99%
“…The electrochemical technique EIS is used as a potential method of detection that offers DNA hybridization sensing up to lower limit of detection 10 nM concentration [9].…”
Section: Introductionmentioning
confidence: 99%